2004
DOI: 10.1023/b:joih.0000045257.83419.75
|View full text |Cite
|
Sign up to set email alerts
|

Improving Access for Latino Immigrants: Evaluation of Language Training Adapted to the Needs of Health Professionals

Abstract: The number of Latinos in North Carolina grew by almost 400% between 1990 and 2000. The rapid change in demographics in this state and other southeastern states has caught healthcare providers unprepared. Lack of ability to communicate with Latino patients may result in errors in diagnosis or reduced compliance with recommended treatments. The Culturally and Linguistically Appropriate Services (CLAS) Standards, published in 2001, mandate culturally and linguistically appropriate services for persons with limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 4 publications
1
18
0
Order By: Relevance
“…Although language barrier has been recognized as a primary issue for immigrants in many studies [6,7,14,15,17-21,28,29], this study interestingly showed that language barrier can be considered a two-sided issue. Some health care professionals mentioned although they knew Farsi they had difficulties to understand some words or context.…”
Section: Discussionmentioning
confidence: 66%
“…Although language barrier has been recognized as a primary issue for immigrants in many studies [6,7,14,15,17-21,28,29], this study interestingly showed that language barrier can be considered a two-sided issue. Some health care professionals mentioned although they knew Farsi they had difficulties to understand some words or context.…”
Section: Discussionmentioning
confidence: 66%
“…8 The Area Health Education Center workshops used a modified Berlitz method and a 360-degree evaluation of eight selected students without prior Spanish training (those with previous Spanish experience were excluded from the evaluation). 12 The pediatric programs showed improvements in patient family satisfaction, and all three suggested that their programs were effective. Two programs received scores of 2 points, the highest rating for continuing education programs.…”
Section: Continuing Medical Educationmentioning
confidence: 94%
“…We found only three published studies: two for pediatric physicians 7,8 and one administered by the Area Health Education Center in North Carolina. 12 Training ranged from 20 to 100+ contact hours. The pediatric programs were evaluated by patient family satisfaction surveys.…”
Section: Continuing Medical Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Acculturative stress studies with Latino immigrants have predominantly been conducted in areas of the U.S. with high Latino immigrant populations such as Texas (Arbona, Olvera, Rodriguez, Hagan, Linares & Wiesner, 2010), Florida (Schwartz, Zamboanga & Jarvis, 2007) and California (Finch & Vega, 2003 states may be plagued with increased obstacles and struggles related to the acculturation process. This is predominantly due to the lack of available supports, unavailability of culturally or linguistically congruent services, and discrimination by receiving communities unfamiliar with the Latino population (e.g., Bender et al, 2004;Prado et al, 2008). Given the way in which the context of reception may shape the acculturation process, it is important to examine ways in which the context of reception influences the acculturative stress of recent Latino immigrants.…”
Section: Researchmentioning
confidence: 99%